School’s outdoor area as an educational and health-promoting resource for young teenagers - Mikalsen, Hilde Kristin; Ninive, Guro; Lagestad, Pål (Frontiers in Education, 2022)
Regular physical activity (PA) is positive for the health of young people, but previous research has indicated that many of them don’t reach the recommended healthy level of PA. Several studies indicate that the PA students get during school hours represents an important part of their total physical activity. The purpose of this study is to examine the relation between the size of the school´s total outdoor area and pupils’ physical activity behaviour during schooltime. ActiGraph GT1M accelerometers were used to measure objectively 12-13-year-old schoolchildren’s minutes of moderate to vigorous physical activity (MVPA) during schooltime. The pupils (n=300, 155 girls and 145 boys) came from 18 primary schools in two medium-sized municipalities in mid-Norway. Linear regression analysis was used to examine the relationship between the schools’ total outdoor area and outdoor area per pupil in relation to pupils’ weekly minutes of MVPA during schooltime. The results show no association with either the schools’ total outdoor area or the outdoor area per pupil, and the pupils’ weekly minutes of MVPA during schooltime. This finding indicates that there are probably factors in the school environment affecting young people's level of activity during schooltime, other than the size of the schools’ outdoor area.